Strategic processing of academic text: identifying a strategic reader / Bromeley Philip and Nelson Anak Martin Noel - Philip, Bromeley; Martin Noel, Nelson (Universiti Teknologi MARA, Kedah, 2017)
The study aimed to explore the strategic processing of an academic text by students to discover the types of strategies employed. The research employed a qualitative case study method to investigate the cognitive processes that the subjects experienced as they were engaged in a reading task. The study was conducted at Universiti Teknologi MARA Sarawak (UiTMS) involving 10 out of 23 students from the Bachelor of Administrative Science (BAS) Programme, where permission was obtained from both the university and the respondents. The number of sample was small because the study focused on individual cases to generate data on strategic processing. The subjects were given an academic text to read in one lecture session and immediately after the silent reading session, the subjects were required to do retrospective written recall protocols (RWRP). The RWRPs of the subjects were inter-rated and analysed for the presence and occurrence of strategies which were identified using the Metacognitive Awareness Reading Strategies Inventory (MARSI) as guideline for interpretation. The findings revealed that the subjects were actively engaging strategic processing; they were using strategies to make meaning from the text. It was found that the subjects used more of global and support strategies rather than problem-solving strategies. Hence, it is possible to say that the subjects were strategic in their reading approach as evidenced from the analysis of the written protocols.